Interaction of Transition Metal Ions with Some Biologically Active Ligands - Basak, Devashish (Asian Journal of Chemistry, 2010)
Mn(II), Co(II) and Ni(II) complexes with biologically active ligands viz. 2-methoxybenzoic acid, 3-methoxybenzoic acid and 4-methoxybenzoic acid have been studied by paper electrophoresis at 25ºC, 35ºC and 45ºC and a fixed ionic strength μ = 0.1 M HClO4. The stability constant values of the complexes have also been reported.